2014
DOI: 10.4081/hpr.2014.1196
|View full text |Cite
|
Sign up to set email alerts
|

A thematic study of the role of social support in the body image of burn survivors

Abstract: There is evidence that social support is important for the development and maintenance of body image satisfaction for people who have sustained burn injuries. This qualitative study explored the specific mechanisms by which social support impacts the body image satisfaction of burn survivors, drawing on nine participants’ in depth accounts. Participants were recruited through a burns unit at a public hospital in South Australia. Interviews were conducted with nine female burn survivors aged between 24 and 65 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
(23 reference statements)
2
5
1
Order By: Relevance
“…The present study showed that perceived social support by friends was directly and positively related to body image in both mastectomy and tumor resection with breast preservation groups. In line with the results of the present study, Hodder et al showed that those with high social support were less focused on burns and their effects and felt more comfortable, and those who received social support from friends continued to play a role in society and had high self-confidence [27]. Merianos et al 's study showed that perceived social support by friends has a significant and positive correlation with students' body image [28].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The present study showed that perceived social support by friends was directly and positively related to body image in both mastectomy and tumor resection with breast preservation groups. In line with the results of the present study, Hodder et al showed that those with high social support were less focused on burns and their effects and felt more comfortable, and those who received social support from friends continued to play a role in society and had high self-confidence [27]. Merianos et al 's study showed that perceived social support by friends has a significant and positive correlation with students' body image [28].…”
Section: Discussionsupporting
confidence: 89%
“…Those with low social support felt more inferior and suffer. The results of another study indicate the positive effect of family social support on increasing body satisfaction [27].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As a result, the tool was designed to focus on social support, coping strategies, appearance concerns, traumatic stress symptoms and prior psychopathology. 7,[28][29][30][31][32][33] During a trial period, the questionnaire was revised and items were removed based on patient feedback and the balance between quality of the information generated, patient burden and clinician time. Only items with face validity were retained in the final questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Pawijit et al, (2017) explained the mediating paths between social anxiety and BID by which the individual's self-focused thinking can contribute to fear of negative evaluation which by itself can lead to BID. While protective factors against BID remain blurred, social support has been one of the factors negatively associated with BID and related mental issues (Ehlke et al, 2020;Hodder et al, 2014). According to Meyer (2003) theory, the impact of minority stress on mental health can be diluted through social support.…”
Section: Sexual Minorities and Body Image Dissatisfactionmentioning
confidence: 99%